Combined IgE neutralization and Bifidobacterium longum supplementation reduces the allergic response in models of food allergy - Seong Beom An; Bo-Gie Yang; Gyeonghui Jang; Do-Yeon Kim; Jiyoung Kim; Sung-Man Oh; Nahyun Oh; Sanghee Lee; Ji-Yeong Moon; Jeong-Ah Kim; Ji-Hyun Kim; Yoo-Jeong Song; et al. (Nature Communications, 2022)
IgE is a critical component of the allergic response and therapeutic targeting can alleviate symptomology. Here the authors propose the combined use of Bifidobacterium longum and a FcεRIα extracellular domain linked to a IgD/IgG4 hybrid Fc domain fusion protein called IgETRAP and show reduction of mast cell and IgE levels in models of food allergy.